2014
DOI: 10.1159/000365577
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation of the Thalamic Ventral Lateral Anterior Nucleus for DYT6 Dystonia

Abstract: Background: A missense mutation of the THAP1 gene results in DYT6 primary dystonia. While deep brain stimulation (DBS) of the internal globus pallidus (GPi) is effective in treating primary dystonia, recent reports indicate that GPi DBS is only mildly effective for DYT6 dystonia. Objective: To describe a patient with DYT6 dystonia who underwent thalamic ventral lateral anterior (VLa) nucleus DBS. Patient: A 35-year-old Japanese man had been experiencing upper limb dystonia and spasmodic dysphonia since the age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 19 publications
3
29
0
Order By: Relevance
“…This sustained effect also explains the persistent good motor response when the battery charge is low, and the speech disturbance was attributed to the progressiveness of dystonia. Dysarthria happened when a different configuration in the GPi was tested, as observed by Mure et al 17 in a patient with DYT6 primary dystonia, although Gruber et al 6 only noticed this adverse event in Vim DBS.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…This sustained effect also explains the persistent good motor response when the battery charge is low, and the speech disturbance was attributed to the progressiveness of dystonia. Dysarthria happened when a different configuration in the GPi was tested, as observed by Mure et al 17 in a patient with DYT6 primary dystonia, although Gruber et al 6 only noticed this adverse event in Vim DBS.…”
Section: Discussionmentioning
confidence: 92%
“…It modulates pallidal bursts to the thalamocortical relay, 7,15 but it is compromised by the abnormal plasticity in dystonia. 6,7 Despite the reference of Vop connection to the cerebellum, 5,17,21 studies with its direct reading, 11,15 including an analysis of pallidal stimulation effects on Vop, showed that "Vop is a major target of GPi efferents" 6,11,15,16 and attributed to Vim the cerebellar connection. 11,15,16 In another study analyzing the pallidal-thalamic circuit, after GPi and Vim DBS for hemidystonia, a 5-to 18-Hz activity was observed, but some of the readings recorded at the Vim could have originated from the adjacent pallidal-receiving thalamus (the Vop).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations